2017
DOI: 10.1016/j.apenergy.2017.06.084
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the octane response of gasoline/ethanol blends

Abstract: h i g h l i g h t s New experimental data for five components with ethanol addition are collected. A new blending rule for PRF, TPRF and multi-components + ethanol octane numbers is proposed. The developed model is validated against real gasoline fuel data. Methods to optimize the octane response due to ethanol addition are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 72 publications
4
50
0
Order By: Relevance
“…Similar antagonistic behavior has also been observed for methyl acetate [12]. Foong et al [11] reported that nonlinearity was reduced when scaled on a molar basis, because ethanol--being a lighter molecule-has a large mole fraction for a given mass fraction [13][14][15][16][17][18]. Recently, Waqas et al studied the blending effect of ethanol addition with several base-fuels and found synergistic blending boosting behavior when operating a CFR engine in SI--as well as in the HCCI mode--in terms of the blending octane number (BON) [7,19].…”
Section: Introductionsupporting
confidence: 56%
“…Similar antagonistic behavior has also been observed for methyl acetate [12]. Foong et al [11] reported that nonlinearity was reduced when scaled on a molar basis, because ethanol--being a lighter molecule-has a large mole fraction for a given mass fraction [13][14][15][16][17][18]. Recently, Waqas et al studied the blending effect of ethanol addition with several base-fuels and found synergistic blending boosting behavior when operating a CFR engine in SI--as well as in the HCCI mode--in terms of the blending octane number (BON) [7,19].…”
Section: Introductionsupporting
confidence: 56%
“…The predictive capability of methods like PLS and MLR was found to be limited when applied to RON and MON, especially in gasolines containing ethanol [23]. There is a non-linear increase in RON and MON of a gasoline when ethanol (an octane booster) is blended [26]. Therefore, ANN was employed to effectively capture non-linear and complex relationships between input features and the output of interest (RON and MON).…”
Section: Introductionmentioning
confidence: 99%
“…The mean absolute error of prediction for RON and MON for the test set was found to be 1.2 for both, which is near the vicinity of experimental error (0.7) while measuring per the ASTM standard CFR methodology.As seen from figure 13, there is a poor comparison between the measured and MLR predicted values, wherein R 2 for RON and MON are 0.52 and 0.51, respectively. This is mostly due to the antagonistic effect of ethanol addition[23,24,26,63,66], which a linear MLR model is unable to capture.Octane sensitivity (OS)[67], defined as the difference between RON and MON, is a measure of the difference in auto-ignition chemistry between that of the fuel and PRF. Highoctane sensitive fuels are more resistant to knock and are of interest in modern SI engines.…”
mentioning
confidence: 99%
“…Similarly, a mathematical formulation is needed to estimate the auto-ignition characteristics of a fuel blend. Despite several studies suggested complex mathematical formulations [51,52,53,54,55], Pera et al [37] suggested a simpler linear approach proven to be effective for surrogates having an aromatic content (toluene) up to 35 vol%. For this reason, a linear weighted average approach, using molar fractions as weights, is used to quantitatively evaluate the auto-ignition characteristics in the present study.…”
Section: Gasoline-ethanol Fuel Surrogate Formulationmentioning
confidence: 99%
“…Generated surrogates are able to reproduce this non-linear behavior consistently. Although [53,54,55] proposed a valid and detailed approach for targeting octane numbers non-linear behavior when ethanol is added to hydrocarbon mixtures, Pera et al [37] demonstrated that a linear mole-weighted mixing rule is able to provide very close estimations of RON and MON compared to the non-linear approaches proposed in [41,52, 53, 54, 55.]. This comparison carried out by Pera et al [38], highlighted a negligible deviation of the linear rule within 35%vol content, which is the standard aromatic content for commercial gasoline.…”
Section: Gasoline-ethanol Fuel Surrogate Formulationmentioning
confidence: 99%